86.5k views
5 votes
Express the sum in simplest form 1/x + 1/y PLEASE!!!!!! I’m trying to graduate

User XGouchet
by
5.9k points

2 Answers

5 votes

Answer:

(x-y)

Explanation:

convert the numerator and denominator so they can be written as single fractions.. (x/y) -(y/x) = (x/y)*(x/x) - (y/x)*(y/y) = (x^2 -y^2) / (xy) ; now the denominator (1/y)*(x/x) + (1/x)*(y/y) = (x+y)/ (xy) ; now remember that dividing by a fraction is the same as multiplying by the reciprocal so your problem now becomes [(x^2 -y^2)/(xy)] * [(xy)/(x+y)] = (x^2-y^2) / (x+y) = [(x+y)(x-y)]/(x+y) = final answer (x-y)

User Sandwood
by
4.5k points
3 votes


(y + x)/(xy)

hope this helps!

User AngelCastillo
by
5.7k points